IMPLEMENTASI PROGRAM JOB FAIR PADA DINAS KETENAGAKERJAAN DAN TRANSMIGRASI PROVINSI BENGKULU - Dedi Setiadi; Djonet Santoso; Yorry Hardayani (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2024)
Job Fair program of the Manpower and Transmigration Office of Bengkulu Province is present with the aim of reducing the increasing unemployment rate, namely by bringing together job seekers with companies that are opening job vacancies. The purpose of this study is to know, understand and describe the implementation of the Job Fair program of the Manpower and Transmigration Office of Bengkulu Province. To determine the achievement of these goals, this study uses research aspects from Nugroho's implementation theory (2017), which consists of Pre-Implementation, Implementation, and Post-Implementation stages. The method used is qualitative descriptive with data collection using observation, interview and documentation methods. The results of this study show that the implementation of the Job Fair program at the Manpower and Transmigration Office of Bengkulu Province has not run optimally. This is because the evaluation aspect has not run optimally, namely in the process and final achievement (output) where the Manpower and Transmigration Office of Bengkulu Province does not have data on the number of people accepted for work in the Job Fair program, so it cannot measure the success of the implementation of the Job Fair programIn reducing unemployment in Bengkulu Province.